Integrating Multidisciplinary Individualized Medication Recommendations Into the Traditional Pharmacists' Consultation Method: A Retrospective Study Using Propensity Score Matching Analysis. (23rd May 2022) - Fan, Xiucong; Chen, Danxia; Bao, Siwei; Bai, Rong; Fang, Fang; Dong, Xiaohui; Zhang, Yuyi; Zhang, Xiaogang; Ma, Yabin; Zhai, Xiaobo
Chinese clinical pharmacists consider improving the quantity and quality of consultations to be an important task in providing better pharmaceutical care. To achieve this goal, we developed a clinical pharmacist consultation method using multidisciplinary individualized medication recommendations (MIMRs) and studied the effects of its implementation. A retrospective study of 812 clinical pharmacist-led consultations was conducted. In the pre-intervention group, medication advice was given based on the purpose of the consultation. In the post-intervention group, a consultation method using MIMRs was implemented, in which clinical pharmacists with specialties in anticoagulation, gastroenterology, and nutrition were asked to give individualized medication recommendations. Outcomes, including the effectiveness rate of consultations (ERC) and acceptance rate of consultations (ARC), were compared between the two groups using propensity score matching method. Patterns and numbers of consultations and individualized medication recommendations were also compared. The results showed that the ERC in the post-intervention group compared with the ERC in the pre-intervention group was 83.3% vs 74.0%, respectively (P < .05). Significant difference was also shown between the two groups in ARC (98.4% vs 92.2%, P < .05). The total number of consultations increased, as did the number of general consultations, multidisciplinary/difficult consultations, anti-infection consultations, and non–anti-infection consultations specifically. As a result, we proposed that the implementation of MIMRs can improve the effects of treatment and increase the number of consultations by pharmacists, which is worthy of further promotion to better serve physicians and patients.